TikTok sebagai Media Komunikasi dan Edukasi dalam Upaya Pelestarian Lingkungan di Kalangan Anak Muda : Studi dalam Akun Tiktok @pandawara_group - Rustam , Nurul Khairunnisa (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
The results of this research show that in educating TikTok social media users, @pandawara_group uses persuasive communication models, including association techniques, integrity techniques, and organization techniques. This research shows three indicators of Pandawara's success in carrying out the persuasive communication process, including credibility, identification and similarity. The theory used in examining netizen responses to this account uses the Strong Impact theory. The form of response given by netizens shows support, requests, constructive questions, and the emergence of accounts similar to the @pandawara_group account. The implication of this research, namely the understanding that TikTok is only for entertainment, can be refuted by this research which shows concrete facts about TikTok as a medium of communication and education